2004
DOI: 10.1007/s11940-004-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic generalized epilepsy

Abstract: Successful treatment of idiopathic generalized epilepsy begins with accurate seizure classification. Seizure types, such as absence, myoclonic, and primary generalized tonic-clonic seizures (PGTCS), often can be classified based on a detailed history and inter-ictal electroencephalogram (EEG). Ideally, patients can be classified into specific epilepsy syndromes, such as childhood absence epilepsy, juvenile myoclonic epilepsy (JME), or generalized tonic-clonic seizures on awakening. Idiopathic generalized epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 31 publications
(10 reference statements)
0
16
0
2
Order By: Relevance
“…It is generally agreed that valproate is the current treatment for JME and it is effective in as many as 80–85% of patients (Gelisse et al, 2001). Among newer AEDs, lamotrigine and topiramate have been proposed in the treatment of JME, but controlled trials are lacking and the results are not focused on EEG abnormalities (Panayiotopoulos 2001; Sullivan & Dlugos, 2004; Sousa Pda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally agreed that valproate is the current treatment for JME and it is effective in as many as 80–85% of patients (Gelisse et al, 2001). Among newer AEDs, lamotrigine and topiramate have been proposed in the treatment of JME, but controlled trials are lacking and the results are not focused on EEG abnormalities (Panayiotopoulos 2001; Sullivan & Dlugos, 2004; Sousa Pda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among newer antiepileptic drugs (AEDs), lamotrigine, topiramate, and zonisamide have been controversially reported to be effective in JME on the basis of uncontrolled studies in small groups of patients (Carrazana & Wheeler, 2001; Panayiotopoulos, 2001; Sousa Pda et al, 2005; Sullivan & Dlugos, 2004; Kothare et al, 2004). In these studies no electrographic results were reported.…”
mentioning
confidence: 99%
“…33 We did not find differences in volumes between those not treated with valproate and those treated with valproate, commonly the first-line treatment of choice in IGE. 34 In addition, no volume differences were evident between children whose first medication was valproate and children whose first medication was not valproate. If AED effects were present, they were uniform across subjects and not dependent upon drug type.…”
Section: Aed Frequencymentioning
confidence: 96%
“…Based on clinical trial data, mechanisms of action, and clinical experience, certain AEDs are generally preferred for focal epilepsy (CBZ, OXC, PHT) and other AEDs are preferred for generalized epilepsy (VPA, ETX, LTG, TPM). 1,2 With rare exceptions, such as VGB as the preferred AED for infantile spasms due to tuberous sclerosis, 3 etiology of epilepsy plays little or no role in AED selection. Similarly, since studies have not yet begun to address genetic determinants of drug efficacy, pharmacogenetics also currently plays no role.…”
Section: Impact Of Pharmacogenetics On Antiepileptic Drug Selectionmentioning
confidence: 99%